Detection of Hyaluronidase and Streptokinase Virulence Factors from Streptococcus pyogenes - Ahmed, Yasameen T; Zbar, Nedhaal S; Al-Shaibani, Abdulwahid B (Al-Nahrain Journal of Science, 2018)
This study was designed to detect and evaluate two of the virulence factors, hyaluronidase and streptokinase, produced by local isolates of Streptococcus pyogenes obtained from children suffering from pharyngitis. Results showed that 30 out of 135 suspected bacterial isolates obtained from 85 pharyngeal swapswere able to produce hemolysis and considered to belong to Group A streptococci. Only 4 of these were sensitive to bacitracin, and were regarded as S. pyogenes. All four isolates were able to produce streptokinase by using the casinolytic assay method, only 3 of them showed ability to produce hyaluronidase by using two methods; plate assay method and turbidity reduction assay method.